Production of bio-oil from sewage sludge: A review on the thermal and catalytic conversion by pyrolysis. (December 2020) - Haghighat, Manouchehr; Majidian, Nasrollah; Hallajisani, Ahmad; samipourgiri, Mohammad
Graphical abstract: Highlights: Pyrolysis is an effective way to convert sewage sludge into biofuels. Bio-oils from direct pyrolysis are not suitable for consumption as automotive fuels due to their high water content and oxygen content. The effect of various factors on the production of bio-oil from pyrolysis. Investigation of physical and chemical characteristics of sewage sludge. Investigating the possibility of using bio-oil from pyrolysis as car fuel and the challenges ahead. Abstract: The reduction of energy sources, environmental and destructive pollution caused by the combustion of fossil fuels and urban sewage wastes, has created a situation that researchers are thinking about a solution to two problems simultaneously. There are several processes for converting sewage sludge to energy. Pyrolysis is considered one of the processes of interest. The products obtained and the characteristics of each product depend on the pyrolysis operating factors, such as temperature, residence time, heating rate, specifications of the reactor, and the catalyst. The amount of oxygen and water in bio-oils is high and its viscosity is high, therefore are unstable in terms of oxidation. Therefore, it is necessary to improve it. Most liquid bio-oil products are obtained when the bio-char production is minimized. This is done at high temperatures and heating rate temperatures around 1000 °C/S with rapid cooling. Fluidized bed reactors are the most economically suitable reactors for rapid pyrolysis of sewage sludge with high bio-oil production efficiency. The cost of raw materials is 80% of the total cost of bio-oil production, so, the use of sewage sludge as feed for the pyrolysis process to produce bio-oil reduces its cost and makes its production economically competitive with fossil diesel.